(untitled) (CIPEEX, 2025)
This experience report addresses the interdisciplinary project “Mostra Psi,” a semesterly event organized by the Psychology program at UniEVANGÉLICA – Anápolis, which represents the culmination of extension activities, internships, and interdisciplinary projects from integrative courses. The objective is to present the pedagogical and formative relevance of Mostra Psi in consolidating innovative and integrative academic practices. The method consisted of a systematic description of the experience accumulated across successive editions of the event, including collegiate organization, the definition of semester themes, and the presentation of diverse academic productions. Students from all program levels participated, producing expanded abstracts, systematic reviews, interactive galleries, panels, informational booklets, and pedagogical stations, according to their level of complexity and academic maturity. The results indicate that Mostra Psi constitutes a privileged space for integration between students and faculty, encourages research, and develops skills that go beyond the classroom, fostering the articulation between theory and practice. It is concluded that the experience consolidates itself as an effective formative strategy, strengthening the indissociability between teaching, research, and extension, while contributing to a critical, reflective education committed to social demands.